Structural Reform Priorities for Brazil - Biljanovska, Nina (IMF Working Papers; Working Paper ;, 2018)
Over the last few decades, Brazil has experienced relatively weak economic growth due to stagnant productivity. To boost productivity, Brazil should embark on an ambitious structural reform process. In doing so, it is crucial that authorities select a few reform priorities to avoid dispersing political capital on an overly broad reform agenda. The paper aims to identify Brazil's reform priorities in two steps. First, it estimates the impact that different reforms have on Brazil's productivity. Second, it analyzes survey data to assess the extent of public support for reforms. The results show that banking sector reforms would generate the largest productivity gains and have the highest level of public support. Moreover, they would also be relatively easy to legislate and generate significant fiscal savings.